An investigation of different ceramic coating thermal properties - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
In the present study, ceramic coated onto metals are applied by plasma-spraying technique. Three types of ceramic coating (Al2O3, Cr2O3, ZrO2) with and without bonding coating were applied to cast iron materials. The thermal torch and the thermal shock tests were conducted to coatings which were made according to the international standards. At the end of the tests, the most suitable ceramic coating was determined. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: ceramic coating; thermal properties; plasma spray technique; ZIRCONIA CERAMICS; WEAR BEHAVIOR; MECHANICAL-PROPERTIES; BARRIER COATINGS; FRICTION; STRENGTH; STEEL; OXIDE; TZP